The influence of profitability, liquidity, firm size, tax avoidance, and financial distress on the timeliness of financial report submission - Nanda Pratiwi, Dyah Ayu Novia; Fauzan, Fauzan (Institute of Computer Science (IOCS), 2024)
This study investigates the influence of profitability, liquidity, firm size, tax avoidance, and financial distress on the timeliness of financial report submissions in industrial companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. Utilizing a quantitative approach, the study analyzes secondary data from the annual reports of 42 companies selected through purposive sampling. The dependent variable is the timeliness of financial report submission, while the independent variables include profitability (measured by ROA), liquidity (measured by CR), firm size (calculated as the natural logarithm of total assets), tax avoidance (CETR), and financial distress (DER). Descriptive statistics and multiple linear regression were used to examine the relationships between these variables. The findings indicate that liquidity is the only factor with a significant impact on timeliness, while profitability, firm size, tax avoidance, and financial distress do not show a significant effect. These results suggest that efficient liquidity management is critical for ensuring timely report submissions, which can enhance financial transparency and market efficiency. This research contributes to the financial reporting literature by emphasizing liquidity's role in reporting practices, offering practical implications for companies and regulators to prioritize liquidity management. The study also acknowledges its limitations, including its narrow focus on industrial companies and a short study period, and recommends further research to explore a broader range of sectors, longer timeframes, and additional influencing factors.